Islamic Religious Education Learning and Trends in the Use of Artificial Intelligence: Pembelajaran Pendidikan Agama Islam Dan Tren Penggunaan Artificial Intelligence - Eneng Humaeroh (ASIAN: Indonesian Journal of Learning Development and Innovation, 2023)
Artificial intelligence (AI) integrated into various media has the potential to create intelligent robots that can facilitate learning, although its use requires adaptation and specific skills. AI does not replace the role of human learning but can streamline access to information, enhance knowledge, and improve the efficiency of learning. The trend of using AI in education has the potential to advance learning technology, which can impact learning outcomes, effectiveness, and innovative capabilities. However, the use of AI also affects social phenomena in education and inevitable social changes, influencing not only human behavior but also the overall social system. This study aims to uncover the phenomenon of AI in the era of digital disruption and the trends in AI usage in Islamic Religious Education (PAI) learning on campuses using a phenomenological approach based on existing literature